Direct‐Acting Antiviral Agents for the Hepatitis C Virus‐Infected Chronic Kidney Disease Population: The Dawn of a New Era. Issue 1 (January 2016) - Kusnir, Juan; Roth, David
Abstract: The introduction of direct‐acting antiviral (DAA) agents with cure rates of >90% has changed the treatment of hepatitis C virus (HCV) in dramatic fashion. An extensive literature has documented the efficacy of these agents in the general population; however, patients with chronic kidney disease have been largely excluded from these trials. Recently published studies conducted in patients with chronic kidney disease are now demonstrating that the DAAs will also offer safe and effective therapy for the HCV‐infected patient with CKD as well. As effective treatment protocols are offered to larger numbers of HCV‐infected CKD patients, the decision regarding when is the most opportune time to treat, especially for the patient being considered for kidney transplantation will become of greater significance. Nephrologists will need to take a lead in these clinical decisions as obtaining a sustained viral response prior to transplant will effectively eliminate the patient as a candidate to receive a kidney from a hepatitis C virus‐positive donor and the benefit of the shorter waiting times accompanying this strategy.